OPTIMIZING GROWTH AND SURVIVAL OF MILKFISH (CHANOS CHANOS) FRY BY OLIVE OIL SUPPLEMENTATION IN COMMERCIAL FEED (Journal of Fish Nutrition, 2024)
This study aims to evaluate the effect of olive oil supplementation in commercial feed on the growth and survival rate of milkfish (Chanos chanos) fry. The research used a Completely Randomized Design with five treatments and three replications: control without oil addition (A), fish oil 1 ml/30 g feed (B), olive oil 0.5 ml/30 g feed (C), olive oil 1 ml/30 g feed (D), and olive oil 1.5 ml/30 g feed (E). The results showed that olive oil supplementation significantly affected growth and survival (p
Keywords: Chanos chanos; fish oil alternative; growth performance; olive oil; survival rate